Instructional Alignment as a Measure of Teaching Quality. (December 2014) - Polikoff, Morgan S.; Porter, Andrew C.
Recent years have seen the convergence of two major policy streams in U.S. K–12 education: standards/accountability and teacher quality reforms. Work in these areas has led to the creation of multiple measures of teacher quality, including measures of their instructional alignment to standards/assessments, observational and student survey measures of pedagogical quality, and measures of teachers' contributions to student test scores. This article is the first to explore the extent to which teachers' instructional alignment is associated with their contributions to student learning and their effectiveness on new composite evaluation measures using data from the Bill & Melinda Gates Foundation's Measures of Effective Teaching study. Finding surprisingly weak associations, we discuss potential research and policy implications for both streams of policy.